USE OF THE INFORMATION SYSTEM RESEARC IN A HEALTHCARE INSTITUTION - Meirule, Laila; Ežmale, Sandra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The author of the study studies the functional adequacy of information systems in a healthcare company SIA "Preiļu slimnīca". By studying both information systems integrated in the company, the author has compared both systems, as a result of which he has developed proposals for improving the sustainable development of the systems.